Lectin binding sites on the plasma membranes of Orthoptera Tettigonioidea spermatodesms. Issue 11 (25th June 2020) - Pecoraro, Roberta; Scalisi, Maria Elena; Brundo, Maria Violetta
Abstract: In many Vertebrate and invertebrate, the interaction mechanisms among gametes are based on a high affinity and specificity of recognition and link between specific saccharidic residues and receptors present on the surface of gametes. Literature data also suggest that Insects could use this strategy. In particular, Orthoptera Tettigoniidae spermatodesms and sperms undergo radical changes passing through the male to the female genital tracts that may be interpreted as well as a capacitation process. These changes could also concern the presence and distribution of surface glycoconjugates. Our study aims to highlight the presence and distribution of saccharide residues on the spermatozoa surface in five species of Orthoptera Tettigoniidae using a battery of lectins Fluorescein Isothiocyanate Conjugated and Gold Conjugated. The results of this investigation have shown that on the surface of the male gametes are present saccharide residues whose nature and distribution are species‐specific, during their transfer to the female genital tract, they significantly undergo a change. These results let us hypothesize that also for this group of Insects, the glycoconjugates play a significant role in the process of interaction between gametes. Abstract : In Orthoptera Tettigoniidae spermatodesms and sperms are structurally different in male and female genital tracts. Spermatodesms and sperms differences concern also the presence and distribution of surface glycoconjugates. Glycoconjugates have a significant role in fertilization.